Promoting Effect of Ni(OH)2 on Palladium Nanocrystals Leads to Greatly Improved Operation Durability for Electrocatalytic Ethanol Oxidation in Alkaline Solution. Issue 37 (1st August 2017) - Huang, Wenjing; Ma, Xian‐Yin; Wang, Han; Feng, Renfei; Zhou, Jigang; Duchesne, Paul N.; Zhang, Peng; Chen, Fengjiao; Han, Na; Zhao, Feipeng; Zhou, Junhua; Cai, Wen‐Bin; et al.
Abstract : Most electrocatalysts for the ethanol oxidation reaction suffer from extremely limited operational durability and poor selectivity toward the CC bond cleavage. In spite of tremendous efforts over the past several decades, little progress has been made in this regard. This study reports the remarkable promoting effect of Ni(OH)2 on Pd nanocrystals for electrocatalytic ethanol oxidation reaction in alkaline solution. A hybrid electrocatalyst consisting of intimately mixed nanosized Pd particles, defective Ni(OH)2 nanoflakes, and a graphene support is prepared via a two‐step solution method. The optimal product exhibits a high mass‐specific peak current of >1500 mA mg −1 Pd, and excellent operational durability forms both cycling and chronoamperometric measurements in alkaline solution. Most impressively, this hybrid catalyst retains a mass‐specific current of 440 mA mg −1 even after 20 000 s of chronoamperometric testing, and its original activity can be regenerated via simple cyclic voltammetry cycles in clean KOH. This great catalyst durability is understood based on both CO stripping and in situ attenuated total reflection infrared experiments suggesting that the presence of Ni(OH)2 alleviates the poisoning of Pd nanocrystals by carbonaceous intermediates. The incorporation of Ni(OH)2 also markedly shifts the reaction selectivity from the originally predominant C2 pathway toward the more desirable C1 pathway, even at room temperature. Abstract : A hybrid electrocatalyst material is reported, which features small Pd nanoparticles abundantly interfaced with Ni(OH)2 and uniformly supported on graphene nanosheets. The synergy between Pd and Ni(OH)2 leads to dramatically improved electrocatalytic performance of the precious metal for the ethanol oxidation reaction and markedly shifts its selectivity toward the C1 pathway in alkaline solution.